(n, n(n‐1), n‐1) Permutation group codes - Li Peng (Electronics Letters, 2016)
Two different subgroups Cn and Ln of symmetric group Sn are first designed and then to construct a family of permutation group codes Pn with code length n, minimum Hamming distance n − 1, cardinalityn(n − 1) and error‐correcting capability n − 2 is composited.